Landforms as extended composite phenotypes. Issue 1 (14th July 2015) - Phillips, Jonathan D.
ABSTRACT: Biotic influences on geomorphology (and vice‐versa) are ubiquitous. This paper explores whether landforms may be extended (composite) phenotypes of biota, based on four criteria: process–form relationships between biota and landforms; evolutionary synchrony; selective pressure via ecosystem engineering and niche construction; and positive feedback benefitting the engineer organism(s). Coral reefs, peat bogs, biomantles, insect mounds, grassland soils, salt marshes, mangrove swamps, and some vegetation‐dependent sand dune types clearly meet these criteria. Karst landforms, meandering rivers, and tree uprooting pit‐mound systems meet the first three criteria, but positive feedback to engineer organisms has not been established. Research in biogeomorphology will surely identify other extended phenotypes. Implications are that biological evolution will continue to drive landscape metamorphosis, the appearance of new landform types, and presumably the disappearance of extended phenotypes associated with extinct species. Independently of extended phenotypes, tightly‐coupled geomorphological–ecological interactions such as coevolution, and biogeomorphic forms of ecosystem engineering and niche construction are common. The toposphere, encompassing Earth's landforms, is partly a biotic construct. Some elements would be present in an abiotic world, but the toposphere would not exist in anything resembling its contemporary state without a biosphere. This raises important questions with respect to Earth system evolution. The bio, litho‐, atmo‐, hydro‐, topo‐, and pedospheres coevolve at the global scale. Major biotic events have driven revolutions in the other spheres, but the atmosphere and the global hydrological system seem to have been relatively steady‐state at the global scale. The toposphere and pedosphere have not. This suggests that perhaps landforms and soils provide the major mechanisms or degrees of freedom by which Earth responds to biological evolution. Landforms and soils may thus be the 'voice' of the biosphere as it authors planetary change, even if clear biotic signatures are lacking. Copyright © 2015 John Wiley & Sons, Ltd.